Knud Illeris’s Concept of Learning in Working Life by – a Proposal for Adaptation to Qualitative Research on Adult Learning - Radecka, Agata (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The article presents Knud Illeris’s et al. concept of learning in professional life and discusses its individual components. This concept has been adapted for qualitative research on teachers of specialised foreign languages, providing insight into their subjective experiences, which shape their intersubjective world of culture. The aim of the research was to describe and understand changes in role script from several perspectives – from the teacher’s perspective, from a paradigmatic perspective, from a glottodidactic perspective, and from the perspective of the Other. The developed analytical framework (based on Illeris’s concept) can be used in other studies focused on adult individuals and their work-related experiences.